Peran Intolerance of Uncertainty terhadap Depresi pada Individu Dewasa Awal - Nindya Putri Aprodita (Humanitas (Jurnal Psikologi), 2021)
This research aims to determine the role of intolerance of uncertainty on the level of depression of individuals aged 18 to 29 years (emerging adulthood). The participants in this research are 206 people who lives in Jakarta. This research is conducted with a quantitative approach. The level of intolerance of uncertainty (IU) is measured with the IUS-12 scale, while the level of depression is measured with the BDI-II. The role of IU to depression are obtained through linear regression test. The result shows that IU has a significant role (F = 42,645; sig. = 0,000) to depression on the individual aged 18-29 years. Furthermore, the result also show that the prospective IU is the dimension that has a significant role to depression. Keywords: depression, intolerance of uncertainty, emerging adulthood